ZAKAT BANK AS A SHARIA-BASED SOCIAL BANKING MODEL FOR ZAKAT MANAGEMENT - Dahlan, Dahnila (Universitas Airlangga, 2018)
This study aims to construct a model for zakat management based on the concept of a bank. As a country with a Muslim majority, Indonesia has great potential for zakat, which requires professional management. Appropriate zakat management is expected to empower mustahik (recipients) to become independent. The research methodology used is a qualitative approach with descriptive analysis techniques. Based on the analysis results, the bank concept used as a model is a social bank based on sharia principles, hereinafter referred to as a zakat bank. This zakat bank will manage zakat funds as a pooling fund and distribute them to its customers. The customers of the zakat bank are the poor. The distribution of zakat to poor customers will be carried out in three stages, namely: (i) initial stage, (ii) intermediate stage, and (iii) independent stage. When customers reach the independent level, they are no longer entitled to receive zakat, so they will partner with Islamic banks. When customers reach the independent stage, they shift their role from being mustahik (recipients) to muzakki (givers). Keywords: Zakat, Social Bank, Sharia Bank, Zakat Bank, Zakat Productive